2021
DOI: 10.1007/s10072-021-05249-4
|View full text |Cite
|
Sign up to set email alerts
|

Othello syndrome in Parkinson’s disease: a systematic review and report of a case series

Abstract: Introduction Psychosis in Parkinson’s disease (PD) is common and consists of hallucinations, illusions, and delusions. Among the latter, delusional jealousy, also named Othello syndrome (OS), might impair the quality of life of both patients and their partners. We aimed to perform a systematic review and report a series of PD patients presenting with OS. Methods A systematic review research was performed in PubMed database, excluding non-English articles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Although further studies are needed to determine the absolute risk increase of developing delusional jealousy after taking a dopamine agonist, treatment with these medications may be a risk factor for developing the disorder. This is supported by the findings that delusional jealousy occurs at an increased rate (5%) in patients with PD who are prescribed dopamine agonists,10 and that 64%–100% of patients with PD with delusional jealousy have been treated with a dopamine agonist 15 16. It has been postulated that the behavioural side effects of dopamine agonists such as aggression and psychosis are mediated by D2-receptor agonism; these receptors are implicated in reward and reinforcement neural pathways, and it is via antagonism of these receptors that antipsychotic drugs exert their effects 8.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Although further studies are needed to determine the absolute risk increase of developing delusional jealousy after taking a dopamine agonist, treatment with these medications may be a risk factor for developing the disorder. This is supported by the findings that delusional jealousy occurs at an increased rate (5%) in patients with PD who are prescribed dopamine agonists,10 and that 64%–100% of patients with PD with delusional jealousy have been treated with a dopamine agonist 15 16. It has been postulated that the behavioural side effects of dopamine agonists such as aggression and psychosis are mediated by D2-receptor agonism; these receptors are implicated in reward and reinforcement neural pathways, and it is via antagonism of these receptors that antipsychotic drugs exert their effects 8.…”
Section: Introductionmentioning
confidence: 84%
“…With particular relevance to this case, dopamine agonist use in PD has been implicated in delusional jealousy,10 hypersexuality11 and impulse control disorders 12 13. Delusional jealousy has an estimated prevalence of 1.1%–7.2% in PD 10 14–16. In systematic reviews of case reports and cross-sectional studies, the majority of patients with delusional jealousy were males in the early-middle stages of the disease and had relatively preserved cognition 15 17.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The association between OS and DDS is uncommonly described. In a systematic review published in 2021, DDS was observed in one out of 32 OS patients 9 . The link of causality remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review published in 2021, DDS was observed in one out of 32 OS patients. 9 The link of causality remains to be determined. For some, both syndromes are assimilated to 'hyperdopaminergic' behaviours sharing the same physiopathology of hyperstimulation of limbic circuits of the basal ganglia, coupled with a lack of cortical inhibition.…”
Section: Discussionmentioning
confidence: 99%